Research of properties of nanoscopic structures - Jovan P. Šetrajčić (Zaštita Materijala)
Aim of this paper is creation of model of ultrathin films, superlattices, nano wires and quantum dots, and investigations microscopic and macroscopic properties of these low-dimensional crystal systems. It was demonstrated that reducing space dimensions and boundary conditions has great influence on the physically relevant properties in these crystal substances. Resonant absorption, different behavior of specific heat and critical superconductive temperatures up to 100 OC were explained.